Local release of siRNA using polyplex-loaded thermosensitive hydrogels. Issue 18 (5th May 2020) - Fliervoet, Lies A. L.; Zhang, Heyang; van Groesen, Emma; Fortuin, Kyra; Duin, Naut J. C. B.; Remaut, Katrien; Schiffelers, Raymond M.; Hennink, Wim E.; Vermonden, Tina
Abstract : An injectable thermosensitive hydrogel to promote local and sustained release of small nanosized (10–20 nm) siRNA polyplexes. Abstract : One of the challenges for the clinical translation of RNA interference (RNAi)-based therapies concerns the deposition of therapeutically effective doses of the nucleic acids, like siRNA, at a local tissue level without severe off-target effects. To address this issue, hydrogels can be used as matrices for the local and sustained release of the siRNA cargo. In this study, the formation of polyplexes based on siRNA and poly(2-dimethylaminoethyl methacrylate) (PDMAEMA)-based polymers was investigated, followed by their loading in a thermosensitive hydrogel to promote local siRNA release. A multifunctional NPD triblock copolymer consisting of a thermosensitive poly( N -isopropylacrylamide) (PNIPAM, N), a hydrophilic poly(ethylene glycol) (PEG, P), and a cationic PDMAEMA (D) block was used to study the binding properties with siRNA taking the non-thermosensitive PD polymer as control. For both polymers, small polyplexes with sizes ranging from 10–20 nm were formed in aqueous solution (HBS buffer, 20 mM HEPES, 150 mM NaCl, pH 7.4) when prepared at a N/P charge ratio of 5 or higher. Formulating the siRNA into NPD or PD polyplexes before loading into the thermosensitive PNIPAM–PEG–PNIPAM hydrogel resulted in a more controlled and sustained release compared to free siRNA release from the hydrogel. The polyplexes were released for 128 hours in HBS, when changing the release medium twice a day, while free siRNA was completely released within 50 hours with already 40% being released after changing the release medium just once. The release of the polyplexes was dependent on the dissolution rate of the hydrogel matrix. Moreover, intact polyplexes were released from the hydrogels with a similar size as before loading, suggesting that the hydrogel material did not compromise the polyplex stability. Finally, it was shown that the released polyplexes were still biologically active and transfected FaDu cells, which was observed by siRNA-induced luciferase silencing in vitro . This study shows the development of an injectable thermosensitive hydrogel to promote local and sustained release of siRNA, which can potentially be used to deliver siRNA for various applications, such as the treatment of tumors.